Species Diversity of Non-Volant Small Mammals Between Lowland and Highland of Gunung Serapi, Kubah National Park, Sarawak - Tingga, Roberta Chaya Tawie; Adrus, Madinah; Azman, Haziq Izzuddin Muhamad (Borneo Journal of Resource Science and Technology, 2021)
The study of non-volant small mammals was conducted at Kubah National Park (KNP), Sarawak for eight days between November 2018 until February 2019. The objective of this study was to determine the species diversity of non-volant small mammals at the highland (>750 – 805 m a.s.l.) and lowland (<200 m a.s.l.) at KNP. The elevation of Gunung Serapi is 911 m a.s.l. but the highest accessible area is at 805 m a.s.l. The distance between two sampling sites is approximately 4.5 km. Humidity and temperature measurement were also recorded at both sites. A total of 50 cage traps were set up at the highland and 50 cage traps at the lowland. The baits that were used in this study were oil palm and banana. A total of 26 individuals from 11 species, eight genera and four families were captured. However, there is no significant difference in species diversity between low and high elevations because the elevation of KNP was not high enough to distinguish species that are highland or lowland specialist.